'Qué barbaridad, son latinos y deberían saber español primero': Language Ideology, Agency, and Heritage Language Insecurity across Immigrant Generations. (22nd February 2020) - Tseng, Amelia
Abstract: This case study examines the consequences of community language attitudes and ideologies on later-generation heritage speakers through qualitative sociolinguistic and discourse analysis of 22 interviews with first- and second-generation Latinos of diverse backgrounds in a major US metropolitan area. The findings show that imposed deficit identities derived from ideologies of language purity, proficiency, and individual agency were misunderstood and stigmatized later-generation heritage speakers, leading to language insecurity and avoidance despite overtly positive attitudes toward Spanish maintenance. Results demonstrate the resilience of prescriptive/purist language attitudes and the tension inherent between these beliefs (albeit couched within positive heritage language attitudes) and speakers' actual bilingualism. Further, they show that the ideologies of individual agency can paradoxically contribute to the imposition of deficit sociolinguistic identities on later-generation speakers and curtail their language use. The study renders visible connections between ideologies of language, identity, and agency and demonstrates how their reproduction within families and communities circumscribes later-generation heritage speakers' linguistic identities and behavior.